KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGATASI PROKRASTINASI AKADEMIK PADA SISWA DI SMK SMTI BANDAR LAMPUNG - Sari, Elsa Novita; Jasmadi; noffiyanti (Universitas Islam Ahmad Dahlan, 2025)
This study examines the effectiveness of group counseling using self-management techniques to overcome academic procrastination, which is the behavior of delaying tasks that can reduce achievement and increase stress, in six students at SMK SMTI Bandar Lampung. Through a descriptive qualitative approach, data were collected from interviews, observations, and documentation of students, guidance counselors, and the principal. The counseling process was carried out through systematic stages, starting from assessment, goal setting, technique application, to evaluation, where students were guided to recognize their habits and the impact of their behavior. The results of the study proved that this intervention was very effective. The six students successfully changed their negative mindsets and behaviors into positive ones. They became more motivated, able to control themselves, and submit their assignments on time, thereby overcoming their academic procrastination. Overall, group counseling with self-management techniques proved to be a successful method not only in raising awareness but also in equipping students with the ability to think critically and consistently manage their academic responsibilities.